Effect of car painting vapours on pulmonary and liver function of Automobile painting worker within Baghdad governorate area - Numan, Ahmad Tarik (AL-Kindy College Medical Journal, 2012)
Background: Automobile spray painting is considered an occupation with a high risk of respiratory impairment and asthma. Exposure to organic solvents used for spraying might be of high risk for development of dysfunction in other organs.Objective: The study was designed to evaluate the pulmonary and hepatic toxicity due to exposure of automobile painters to organic solvents in work places within the Baghdad governorate area.Methods: Thirty cross sectional selected male workers employed in automobile body paint shops in two industrial areas within Baghdad city (Al-Sheikh Omar and Al-Rasheed camp regions) were recruited to the study during the period from March to May 2012. Thirty non-exposed students and employees in the college of pharmacy-University of Baghdad, age matched with workers, were included as control group. Pulmonary function test (PFT) was performed for all subjects using flow spirometry and blood samples were obtained for evaluation of serum transaminases (AST and ALT), in addition to serum levels of total bilirubin and albumin. The results were correlated with age of workers and duration of exposure.Results: The results indicated significant decrease in PFT markers (FVC, FEV1, FEV1/FVC and PEF) compared to control group, while liver function did not significantly affected. Correlation of the PFT markers with age and duration of exposure reveals non significant values.Conclusion: Spray painting is an occupation which involves the risk of respiratory impairment and also confirms the need of regular medical examinations and implementation of appropriate measures to prevent adverse respiratory effects of workplace exposure in automobile spray painters.